Implementation of Teacher Training Model to Improve Primary School English Teachers’ Teaching Ability - Muhammad, Ribeh Najib (DIDAKTIKA : Jurnal Pemikiran Pendidikan, 2026)
The implementation of English as a compulsory subject in primary schools under Indonesia's Merdeka Curriculum has created an urgent demand for competent teachers capable of effectively teaching English to young learners. However, most primary school teachers lack formal English education backgrounds, creating a significant competency gap that threatens instructional quality. This systematic literature review synthesizes and critically analyzes existing research on teacher training effectiveness, specifically focusing on classroom language proficiency and pedagogical competence for teaching English to young learners (TEYL). Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, this review systematically searched Scopus, Web of Science, ERIC, and Google Scholar for peer-reviewed articles published between 2015 and 2024. The findings reveal four major themes: classroom language mastery as a foundational component of effective TEYL instruction, age-appropriate pedagogical competencies tailored to young learners' cognitive and affective characteristics, integration of technology and multimedia resources in primary English education, and persistent challenges and barriers in implementing effective training programs. The review demonstrates that comprehensive training models integrating classroom language, pedagogical strategies, and continuous professional development significantly improve teachers' confidence, instructional quality, and student learning outcomes